Analisis Determinan Kejadian Infeksi Saluran Pernafasan Akut (ISPA) di Wilayah Kabupaten Bogor: Analysis of Determinants of Acute Respiratory Infections (ARI) in the Bogor Regency Area - Nina; Silalahi, Rizma (Journal of Public Health Education, 2022)
Introduction: Based on the Kab. Bogor, Shows that the first top infectious disease in the hospital is Non-Specific Acute Respiratory Infection with a total of 1,436,388 (15.98%), then the second is acute nasopharynx with a total of 1,235,732 (13.75%), and so on followed by other diseases. Based on the results of the above observations, the most influential and possible wide impact on public health is the condition of sanitation and environmental health, namely the problem of household waste. Objectives: The purpose of knowing the results of risk factor analysis with the incidence of acute respiratory infections (ARI) then identifying and prioritizing health problems/implementation achievements and knowing alternative solutions to health problems/achievements of implementing health programs in Bogor Regency in 2020. Method: Descriptive analytics with a population of 19 people Information and data in this study were obtained through field observations, interviews, literature studies to data collection using Google Forms media. The data obtained were then analyzed using the Criteria Matrix Technique (Criteria Matrix Technique) and Ichikawa Diagrams (Fish Bones). Result: Based on the results of the study, there were 4 priority problems, namely it was known that the frequency of littering and burning garbage was 14.4% the frequency of smoking habits in the house was 12.8%. healthy, namely 8.4%, the frequency of air conditions around the house worsening due to pollution is 6.0%. Conclusion: The behavior of littering and the habit of processing waste by burning are problems that we found while observing the environment in the Bogor Regency area, this was due to a lack of knowledge and public awareness about proper and proper waste management. That way, the alternative problem solving that researchers want to do is to run the program "Ready to Prevent ARI with T2M2S (No Burning and Disposing of Garbage Carelessly)".